The International Organization of Production in the Regulatory Void - Philipp Herkenhoff; Sebastian Krautheim (Center for Economic Studies and ifo Institute (CESifo), 2018)
Over the last decades, the internationalization of the value chain has allowed firms to exploit cross-country differences in environmental and labor regulation (and enforcement) in ways that have led to a large number of NGO campaigns and consumer boycotts criticizing `unethical' practices. How do potential `unethical' cost savings on the one hand and the threat to reputation and sales on the other interact with the international organization of production? In this paper we introduce North-South differences in regulation, a cost-saving `unethical' technology and consumer boycotts into a standard property rights model of international production. Contracts are incomplete, so that a firm has limited control over both investments and (un)ethical technology choices of both foreign affiliates and suppliers along the value chain. We show that international outsourcing and `unethical' production are linked through a novel unethical outsourcing incentive, for which we also provide empirical support: a high cost advantage of `unethical' production in an industry and a low regulatory stringency in the supplier's country favor international outsourcing (as opposed to vertical FDI). We also provide a microfounded model of investment and pricing under incomplete contracts when the production technology is a credence characteristic of the final good and an NGO investigates firms and may initiate a consumer boycott.
Keywords: D21; D23; F12; F23; F61; J81; L22; L23; L31; L50; Q53; 330; multinational firms; international outsourcing; property rights theory of the firm; ethical production; labor standards; pollution; consumer boycotts; credence goods; NGOs